Deafult, Seizure, and the Ordnung Principle in Russian Art at the Beginning of the 21st Century - Doronina, Maria A. (Actual Problems of Theory and History of Art, 2024)
The article examines the work of two generations of artists from the 2000s to the 2010s, who sought to interpret the traditions of Western conceptual art and explore the material and formal structures of the corporate world and office life. The purpose of this introductory material is to identify key trends in addressing new types of reading the administrative-bureaucratic discourse of Conceptualism of the 1960s on the territory of artistic life of the last twenty years. Its main goal is to map the key conceptual and event series that illuminated the art of this era. The article examines the works of authors from different generations and schools, but at the same time focuses on the representatives of the younger generation of the 2000s and young artists of the 2010s on the Moscow art scene, who have been engaged in reworking the principles of Western European institutional criticism in a new way. Thus, in the 2000s, the activities of the ABC (Art Business Consulting) group (Maxim Ilyukhin, Mikhail Kosolapov, Natalya Struchkova) acquired some significance. In the 2010s, besides the ASI (Agency of Singular Investigations) art group (Anna Titova, Stanislav Shuripa), associated with the circle of the above-mentioned artists, the most characteristic key representatives of various approaches to the processing of bureaucratic imagery became artists such as Anastasia Ryabova and Kirill Savchenkov. In addition to indicating some of the key projects of the aforementioned artists, the article touches those authors, as well as cultural workers, who were involved in conceptualizing the theme of the workplace and the office during the designated period.